EKSTRAKSI LIKOPEN DARI BUAH TOMAT (Lycopersicum Esculentum) MENGGUNAKAN PELARUT TUNGGAL DENGAN METODE KRISTALISASI ANTISOLVENT - Sola Fide Gavra Tarigan, Deviana C.S. Sinaga, Zuhrina Masyithah (Universitas Sumatera Utara, 2016)
This research was aimed to study the effect of feed and solvent ratio (f/s), antisolvent variety and solvent variety to the extraction of lycopene from tomato (Lycopersicum esculentum)by using single solvent and antisolvent crystalization method. The solvent that used was hexane and ethyl acetate and also methanol and ethanol as the antisolvent. Tomatoes was milled and then extracted. Antisolvent then added to the extract which was obtained. The results show that the more feed and solvent ratio (f/s) the more lycopene obtained. At the ratio of 1:4,5 with hexane as the solvent obtained the highest lycopene yield were 2,7 mg/150 ml and 2,2 mg/150 ml. Whereas at the ratio of 1:4,5 with ethyl acetate as the solvent obtained the highest lycopene yield were 3,2 mg/150 ml dan 2,8 mg/150 ml. By using methanol as an antisolvent, much lycopene would be obtained. By using ethyl acetate as a solvent, much lycopene would be obtained.